Hydrothermal synthesis, structure, and optical properties of pure and silver-doped Bi2MoO6 nanoplates - Anukorn Phuruangrat (2018)
© 2015 Pleiades Publishing, Ltd. The effect of Ag doping on Bi 2 MoO 6 was studied in this research. Ag-doped Bi 2 MoO 6 nanoplates were synthesized by a hydrothermal method at 180°C for 20 h. X-ray powder diffraction (XRD) and selected area electron diffraction (SAED) confirm that the products have orthorhombic Bi 2 MoO 6 structure. Bi 2 MoO 6 nanoplates were detected by transmission electron microscopy (TEM). X-ray photoelectron spectroscopy (XPS) shows peaks with binding energies of 368.84 and 374.87 eV which could be attributed to Ag 3d 5/2 and Ag 3d 3/2 , confirming that Ag is present in the Bi 2 MoO 6 matrix. Raman and FTIR spectra show the vibration of asymmetric and symmetric stretching and bending modes of MoO 6 octahedrons. The optical properties of products were characterized by UV-Vis spectroscopy. They show strong absorption in UV-Vis region.